1999
DOI: 10.1111/j.1095-8649.1999.tb00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of plerocercoids of Triaenophorus crassus in the second intermediate host Coregonus lavaretus and their effect on growth of the host

Abstract: Patterns of accumulation of Triaenophorus crassus in its second intermediate host whitefishCoregonus lavaretus s.l. were studied between 1991 and 1996 from two host populations in two separate areas of Lake Saimaa, Finland. Whitefish were infected commonly with several T. crassus plerocercoids and the parasites were aggregated into the oldest hosts. In one host population the annual parasite accumulation was 0·9 parasites in all host age groups between 3 and 8 years. In the other host population the annual acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
2
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 25 publications
2
37
2
1
Order By: Relevance
“…The back-calculation method is, however, subject to some validation problems (Francis 1990), and does not necessarily result in the actual lengths at given ages. The application of this method for comparisons of host growths between control and parasitized specimens within the same ®sh population as we did in this study thus seems to be entirely adequate (Pulkkinen & Valtonen 1999). The application of this method for comparisons of host growths between control and parasitized specimens within the same ®sh population as we did in this study thus seems to be entirely adequate (Pulkkinen & Valtonen 1999).…”
Section: Scalimetrymentioning
confidence: 63%
See 1 more Smart Citation
“…The back-calculation method is, however, subject to some validation problems (Francis 1990), and does not necessarily result in the actual lengths at given ages. The application of this method for comparisons of host growths between control and parasitized specimens within the same ®sh population as we did in this study thus seems to be entirely adequate (Pulkkinen & Valtonen 1999). The application of this method for comparisons of host growths between control and parasitized specimens within the same ®sh population as we did in this study thus seems to be entirely adequate (Pulkkinen & Valtonen 1999).…”
Section: Scalimetrymentioning
confidence: 63%
“…Spurred by both con¯icting results (see references above) and the work of Pulkkinen & Valtonen (1999) which has shown accelerated growth rates in parasitized ®sh only during the ®rst year of life, we decided to examine the possible effect of parasitism as a function of host age in roach. Spurred by both con¯icting results (see references above) and the work of Pulkkinen & Valtonen (1999) which has shown accelerated growth rates in parasitized ®sh only during the ®rst year of life, we decided to examine the possible effect of parasitism as a function of host age in roach.…”
Section: Introductionmentioning
confidence: 99%
“…Stable isotope turnover is expected to vary with body size or age, with diet components integrated more rapidly into the tissues of fast growing juveniles than those of older specimens [3]. While parasite infection in young fish might increase metabolism, it may also direct energy and other dietary resources away from growth and into immunological defense mechanisms [1316]. This could alter stable isotope turnover rates, though the effects, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…While T. crassus needs a salmonid fish species as a second intermediate host, T. nodulosus can infest 60 fish species belonging to 17 families and 9 orders (Kuperman 1981), yet infection with this latter species is of less importance as the liver is removed prior to consumption (Lahnsteiner et al 2009). Generally, infection with T. crassus weakens fish and lowers their use for restocking due to muscle damage and impaired growth (Rosen and Dick 1984;Pulkkinen and Valtonen 1999). The need for a control strategy is thus clearly evident.…”
Section: Discussionmentioning
confidence: 98%
“…In the intermediate host, plerocercoids of T. crassus and Triaenophorus nodulosus (Pallas 1781) develop in the musculature and liver, respectively (Hoffman et al 1986;Pulkkinen and Valtonen 1999) and may thus be easily identified on the basis of their habitat. On the other hand, procercoids of T. crassus and T. nodulosus as well as those of other closely related species such as Eubothrium sp., Proteocephalus sp., and Diphyllobothtrium sp., all encyst in the body cavity of copepods.…”
Section: Introductionmentioning
confidence: 99%